2014
DOI: 10.1002/adma.201403943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating 3D‐Printed Biomaterials as Scaffolds for Vascularized Bone Tissue Engineering

Abstract: The recent proliferation of three dimensional (3D) printing technologies has allowed the exploration of increasing complex designs, and, furthermore, the consideration of 3D printed constructs for biological applications. However, there is an unmet need for a consistent set of tools for the design and evaluation of these biological 3D printed constructs, particularly as they relate to engineered tissues. For example, identifying the most advantageous construct parameters for the rapid vascularization of an eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
158
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(169 citation statements)
references
References 34 publications
2
158
0
1
Order By: Relevance
“…18,19 Our previous work identifies a set of tools to evaluate 3D printed scaffolds for use as basis for vascularized musculoskeletal tissues; however, we identified that there is a lack of standards that can provide the methodology to evaluate the long-term degradation of absorbable polymers scaffolds. 20 In this work, our motivation was to investigate novel methodology to determine which 3D-printed porous scaffold design would provide long-term mechanical stability during degradation. This long-term mechanical stability would allow for the scaffold to function as a delivery vehicle for a bioactive material that is loaded into the lumen of the porous-walled scaffold.…”
Section: Figmentioning
confidence: 99%
“…18,19 Our previous work identifies a set of tools to evaluate 3D printed scaffolds for use as basis for vascularized musculoskeletal tissues; however, we identified that there is a lack of standards that can provide the methodology to evaluate the long-term degradation of absorbable polymers scaffolds. 20 In this work, our motivation was to investigate novel methodology to determine which 3D-printed porous scaffold design would provide long-term mechanical stability during degradation. This long-term mechanical stability would allow for the scaffold to function as a delivery vehicle for a bioactive material that is loaded into the lumen of the porous-walled scaffold.…”
Section: Figmentioning
confidence: 99%
“…The typical medical applications of 3D printing include preoperative planning and simulation, sharing detailed surgical information before surgery with patients, and the development of individualized implants and prostheses. 9,10 Unquestionably, 3D printing represents a major opportunity for regenerative medicine 11 and has been applied in attempts to address the demand for tissue engineered scaffolds, artificial tissues, and even organs suitable for transplantation. 5 3D printing is a broad concept that can be classified as additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…All the deficiencies significantly decrease nutrient transportation, cell migration and survival 6. Compared with traditional manufacturing technology, 3D bioprinting can provide the ability to construct multiple hierarchical and multi‐scale bone‐like scaffolds with controlled macro shape, porosity and microstructure, thus allowing for patient‐specific fabrication and customized clinical application 7, 8. 3D bioprinting with fused deposition modeling (FDM) has been one of most effective way to make macro‐scale bone implants with high mechanical strength which also contain microstructures with controllable features.…”
Section: Introductionmentioning
confidence: 99%